Description of Diaspidiotus aetnensis sp. n. (Hemiptera: Coccomorpha:Diaspididae) living on endemic birch in Sicily (Italy), with a key to Diaspidiotus species recorded on Betulaceae - Nucifora, Salvatore; Watson, Gillian W.; Russo, Agatino; Mazzeo, Gaetana (Zootaxa, 2020)
The adult female of a new species of armoured scale insect, Diaspidiotus aetnensis Nucifora, Watson and Mazzeo sp. n. (Hemiptera: Coccomorpha: Diaspididae), is described and illustrated. It was collected in Sicily on the endemic birch, Betula aetnensis Raf. (Betulaceae). We provide supplementary notes on Diaspidiotus alni (Marchal), D. wuenni (Lindinger) and D. lenticularis (Lindinger), and a key to the Diaspidiotus species recorded on Betulaceae worldwide.